From Theory to PrACTice: A Cognitive Remediation Program Based on a Neuropsychological Model of Schizophrenia - Fabre, Delphine; Vehier, Aurélie; Chesnoy-Servanin, Gabrielle; Gouiller, Nicolas; D’Amato, Thierry; Saoud, Mohamed (Frontiers in Psychiatry, 2015)
Cognitive dysfunction is one of the hallmark deficits of schizophrenia. A wide range of studies illustrate how it is strongly interconnected to clinical presentation and daily life functioning (see Green, 1996 and Green et al., 2000). Hence, cognition is an important treatment target in schizophrenia. To address the challenge of cognitive enhancement in schizophrenia, a large number of cognitive remediation programs have been developed and evaluated over the past several decades. First, an overview of these programs is presented highlighting their specificity to cognitive deficit in schizophrenia using an integrated method. In this case, cognitive training focuses on enhancing several elementary cognitive functions considered as a prerequisite to social skills or vocational training modules. These programs are based on the neurodevelopmental hypothesis of schizophrenia. However, moderate improvement for patients who benefit from these therapies has been observed as described in Wykes et al review (2011). Next, neuropsychological models of schizophrenia are then presented. They highlight the critical role of the internally generated intentions in appropriate willful actions. The cognitive control mechanism deals with this ability. Interestingly, available cognitive remediation programs have not been influenced by these models. Hence, we propose another alternative to set up a specific cognitive remediation program for schizophrenia patients by targeting the cognitive control mechanism. We describe the PrACTice program which is in the process of being validated.